Trapping of a Highly Reactive Oxoiron(IV) Complex in the Catalytic Epoxidation of Olefins by Hydrogen Peroxide. (14th February 2019) - Engelmann, Xenia; Malik, Deesha D.; Corona, Teresa; Warm, Katrin; Farquhar, Erik R.; Swart, Marcel; Nam, Wonwoo; Ray, Kallol
Abstract: The generation of a nonheme oxoiron(IV) intermediate, [(cyclam)Fe IV (O)(CH3 CN)] 2+ (2 ; cyclam=1, 4, 8, 11‐tetraazacyclotetradecane), is reported in the reactions of [(cyclam)Fe II ] 2+ with aqueous hydrogen peroxide (H2 O2 ) or a soluble iodosylbenzene ( s PhIO) as a rare example of an oxoiron(IV) species that shows a preference for epoxidation over allylic oxidation in the oxidation of cyclohexene. Complex 2 is kinetically and catalytically competent to perform the epoxidation of olefins with high stereo‐ and regioselectivity. More importantly, 2 is likely to be the reactive intermediate involved in the catalytic epoxidation of olefins by [(cyclam)Fe II ] 2+ and H2 O2 . In spite of the predominance of the oxoiron(IV) cores in biology, the present study is a rare example of high‐yield isolation and spectroscopic characterization of a catalytically relevant oxoiron(IV) intermediate in chemical oxidation reactions. Abstract : Ein kompetenter Komplex : Ein Oxoeisen(IV)‐Komplex wurde abgefangen und als kinetisch sowie katalytisch kompetentes Intermediat im [(Cyclam)Fe II ] 2+ /H2 O2 ‐Katalysesystem für die Olefinepoxidierung charakterisiert. Der Komplex ist ein seltenes Beispiel für eine Oxoeisen(IV)‐Spezies mit einer Präferenz für die Epoxidierung gegenüber der allylischen Oxidation.